Pengaruh Kompensasi Finansial, Motivasi dan Komitmen Karyawan Terhadap Kinerja Karyawan - Setyawan, I Komang; Ayu Yayati Wilya, Ida Dewa (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2021)
Good human resource management is the key to the successful achievement of organizational goals. The company’s success in building Jumantik employee performance cannot be separated from the financial compensation given to employees, employee motivation to work and employee commitment. This study aims to determine the effect of financial compensation, motivation and commitment on employee performance. A total of 34 respondents were involved in this study using the census method. A total of 34 respondents were involved in this study using the census method. The data collected through the distribution of questionnaires were tested for validity and reliability, then continued with multiple linear regression analysis techniques. Based on the results of the study, the results obtained: financial compensation, motivation, and commitment have a significant positive effect on employee performance partially and simultaneously. The magnitude of the influence of the independent variable on the performance of Jumantik employees is 71.2%.